step by step explanation please
Attachments:
![](https://hi-static.z-dn.net/files/df3/8d4fcf3330d7734d7a7e7fe2186df817.jpg)
Answers
Answered by
1
Answer: 11
Solution :
6(x-1) = 5(x+1)
6x - 6 = 5x + 5
6x - 5x = 5 + 6
x = 11
(If it helps you please mark as brainliest.)
Answered by
0
Answer:
10
Step-by-step explanation:
think x=0
6(x-1)=5(x+1)
0-1=0+1
-1=+1
Similar questions
Physics,
2 months ago
Math,
4 months ago
CBSE BOARD XII,
4 months ago
Math,
11 months ago
Social Sciences,
11 months ago
Geography,
11 months ago